Deixa-te ficar na minha casa: instalação imersiva sonora - Achando, Inês Sofia Falcão de Gouveia (2021)
Deixa-te ficar na minha casa, aims to transport the sounds of an intimate space to an immersive installation. The house, my house, is the object of study and which I worked on to develop this research and the collection of sound that defines the shape this space. This process results in an installation that proposes to describe a narrative (the memories of this place) and its architectural spatiality (characteristics of this place) through sound design. During the creation of this project, I developed a theoretical research that I present in Chapter 1. The authors and their artworks establish a line of reasoning and discovery of themes that underpin this project, that addressed the issues that arise as the project is designed and requiring more detail due to the plurality of themes it raises. The first part of this research starts from the sound in cinema and from the way sound defines spatiality, through the urban and spatial sound effects and how it influences our relationship with the surrounding environment (sound ambience), how does the reading of these stimuli have a sensory effect in us and in our perception of space. The second part gets closer to the context of this work project and relates the body's sensory perception in space with the consciousness and listening process through this experience of the body in space. Finally, I present a reflection on the relationship between spectator and the work of art where I present a perspective on the position of the viewer towards the artwork, and how people become an actor/actress and co-creator of the artwork itself. The installation Deixa-te ficar na minha casa is a sound experience, where the spectator, from the perspective of a blind eye, enters into a space whose architecture is modelled through sound vibration.